Translocation of inserted foreign epitopes by a channelforming protein - Jakes, Karen S. (The National Academy of Sciences, 1998)
Certain bacterial protein toxins are able to insert themselves into, and at least partially across, lipid bilayer membranes in the absence of any auxiliary proteins, by using unknown mechanisms to overcome the high energy barrier presented by the hydrophobic bilayer core. We have previously shown that one such toxin, colicin Ia, translocates a large, hydrophilic part of itself completely across a lipid bilayer in conjunction with the formation of an ion-conducting channel. To address the question of whether the colicin can translocate any arbitrary amino acid sequence, we have altered the translocated segment by inserting, singly, two different foreign epitopes. Colicins containing either epitope retain significant bactericidal activity and form channels of normal conductance in planar bilayers. Furthermore, antibodies added on the side of the bilayer opposite that to which the colicin was added interact specifically with the corresponding epitopes, producing an inhibition of channel closing. Thus, the inserted epitopes are translocated along with the rest of the segment, suggesting that a surprisingly small part of colicin Ia, located elsewhere in the molecule, acts as a nonspecific protein translocator.